Pengembangan Multimedia Tutorial Untuk Memfasilitasi Kognitif Prosedural - Luluk Pramita Sari; I Nyoman Sudana Degeng; Henry Praherdhiono (JKTP: Jurnal Kajian Teknologi Pendidikan, 2021)
Abstrak: Penelitian  pengembangan bertujuan menghasilkan produk multimedia tutorial yang layak memfasilitasi kognitif prosedural siswa. Penelitian ini ialah  Research and Development. Acuan model yang digunakan yaitu model menurut Lee & Owens. Review produk multimedia tutorial dilaksanakan oleh ahli materi dan ahli media. Uji coba produk dilibatkan oleh 6 audiens kelas V SDN 1 Sumberdadap Tulungagung. Disimpulkan data hasil review produk memperoleh tanggapan positif dalam kategori layak.Abstract: Development research aims to produce multimedia tutorials that are feasible to facilitate student cognitive procedural. This research is Research and Development. The reference model used is the model according to Lee & Owens. Multimedia tutorial product reviews are carried out by material experts and media experts. The product trial was involved by 6 class V SDN 1 Sumberdadap Tulungagung audiences. It can be concluded that the product review data received positive responses in the proper category.